Sociodemographic Characteristics and Level of Adherence to Focused Antenatal Care Guidelines among Nurses and Midwives Working at the Selected Health Facilities at Imenti South Sub-County of Meru County - Mwiti, Glory; Gitonga, Lucy; Gichobi, Beth; Mwikamba, Gilford (Journal of Health, Medicine and Nursing, 2025)
Purpose: Focused antenatal care is essential to improving neonatal and maternal health by preventing, identifying, and treating medical conditions that endanger a pregnant woman’s health besides a fetus. This study aimed to determine nurses’ and midwives’ adherence to set procedures in focused antenatal care. Methodology: The study adopted an analytical cross-sectional research design. It involved 55 nurses and midwives working at the antenatal clinic in the level 4 (sub-county referral) hospitals, level 3 (health centers), and level 2 (dispensaries) in selected health facilities at Imenti-South sub-county facilities of Meru County. A census was done on all nurses and midwives working at selected health facilities in the Imenti-South Sub-County of Meru County. Data was collected using an observational checklist and a researcher-administered questionnaire. Pre-testing of the data collection instruments was done at public health facilities in the Imenti-central sub-county of Meru County. Analysis was carried out using SPSS version 27. Descriptive statistics i.e. mean, standard deviation, percentages, and frequencies were used to analyze data. Quantitative data is presented in the form of tables, charts, and graphs. Findings: The mean age of the participants was 35.91 ±10.92 SD with more than half being less than 36 years (56.4%). The majority were females (60%). About three-quarters had a diploma in nursing. The majority of the facilities were level II (60%). More than half of the nurse-midwives had no in-service training on FANC (72.7%). There were slightly more participants with good adherence to FANC guidelines (50.9%) than those with poor adherence (49.1%). Adherence was significantly associated with the level of the facility (χ2 = 9.894, df=2 and p = 0.007) although it was not a significant predictor of adherence (p>0.05). The percentage of nurse-midwives with good and poor adherence to FANC guidelines was almost equal. Unique Contribution: There is a need to train the nurse-midwives on the current FANC guidelines as well as provide continuous monitoring and evaluation to enhance adherence. The county government in collaboration with the national government should come up with training manuals to train the nurses and midwives on the FANC guidelines.